More on standard single valued neutrosophic metric spaces: More on SVN-metric spaces - Milles, Soheyb; Latreche, Abdelkrim; Barkat, Omar (Journal of Innovative Applied Mathematics and Computational Sciences, 2021)
Recently, we have introduced the notion of standard single valued neutrosophic (SSVN) metric space as a generalization of the notion of standard fuzzy metric spaces given by J.R. Kider and Z.A. Hussain. In this paper, we study the fundamental properties of standard single valued neutrosophic metric spaces. Furthermore, we introduce the notion of continuous mapping and uniformly continuous mapping in standard single-valued neutrosophic metric spaces. To that end, we give a number of properties and characterizations of these notions.